2013
DOI: 10.1158/1078-0432.ccr-13-1763
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide for Treatment of Patients with Metastatic Castration-Resistant Prostate Cancer Who Have Previously Received Docetaxel: U.S. Food and Drug Administration Drug Approval Summary

Abstract: This article summarizes the regulatory evaluation that led to the full approval of enzalutamide (XTANDI, Medivation Inc.) by the U.S. Food and Drug Administration (FDA) on August 31, 2012, for the treatment of patients with metastatic castration-resistant prostate cancer who have previously received docetaxel. This approval was based on the results of a randomized, placebo-controlled trial which randomly allocated 1,199 patients with mCRPC who had received prior docetaxel to receive either enzalutamide, 160 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 9 publications
2
34
0
1
Order By: Relevance
“…The health of the mice was monitored throughout the study by measuring body weights and checking for abnormal behavior, such as lethargy, lack of hydration, and additional signs of weakness. Tumor size was measured twice weekly and tumor volume calculated using the formula: volume ¼ length  width  depth  0.5236 (mm 3 ). Mice were sacrificed 1 hour after the final dose for tissue harvesting.…”
Section: Lactate and Glucose Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The health of the mice was monitored throughout the study by measuring body weights and checking for abnormal behavior, such as lethargy, lack of hydration, and additional signs of weakness. Tumor size was measured twice weekly and tumor volume calculated using the formula: volume ¼ length  width  depth  0.5236 (mm 3 ). Mice were sacrificed 1 hour after the final dose for tissue harvesting.…”
Section: Lactate and Glucose Determinationmentioning
confidence: 99%
“…Although androgen deprivation therapy (ADT), currently the treatment of choice for metastatic prostate cancer, can lead to remissions, tumors frequently return in a form that is highly resistant to ADT and other therapies, that is, metastatic castration-resistant prostate cancer (mCRPC). Although the efficacy of mCRPC treatment has recently been improved by using more powerful chemotherapeutics targeting the androgen receptor (AR) signaling axis, such as enzalutamide (3) and abiraterone (4), the overall survival of patients has only marginally increased (5)(6)(7). Moreover, it is thought that further improved versions of such drugs can promote transdifferentiation of prostatic adenocarcinoma to neuroendocrine prostate cancer, a subtype of the disease that is currently incurable (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the 'classical antiandrogens', enz does not only block androgen binding, but it also inhibits translocation of the AR to the nucleus and impairs AR binding to DNA (Tran et al 2009). It has been approved by the FDA and EMA for treating patients with chemo-resistant CRPC (Ning et al 2013). Further structural optimization for inhibition of proliferation, pharmacokinetics, and in vivo efficacy resulted in the development of a compound called ARN-509 (Fig.…”
Section: Antiandrogensmentioning
confidence: 99%
“…Enzalutamide In patients who progressed during docetaxel therapy, enz has been shown to increase overall survival in comparison with placebo in mCRPC patients in the AFFIRM trial, leading to its FDA approval (Scher et al 2012, Ning et al 2013. A recent report from the AFFIRM trial showed comparable efficacy, safety, and tolerability in patients aged O75 years as well, suggesting its possible future widespread use (Sternberg et al 2014).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Enzalutamide, a small molecule AR antagonist is a once daily second generation AR signaling inhibitor that was approved by the FDA in 2012 for the treatment of mCRPC post-chemotherapy with docetaxel 63. Given that the AR transcription program remains active despite emergence of castration resistance,64 this property has been exploited to screen for anti-androgens with specific ability to bind and inhibit the AR without the agonistic effects 65…”
Section: Review Of Pharmacology Mode Of Action and Pharmacokineticsmentioning
confidence: 99%